Integrative analysis of single-cell and bulk RNA sequencing reveals the oncogenic role of ANXA5 in gastric cancer and its association with drug resistance - Chen, Denggang; Zhang, Peng; Gong, Li; Wei, Hailang; Yu, Guanghui; Zhang, Tingting; Bai, Chen (Frontiers in Immunology, 2025)
BackgroundGastric cancer (GC) remains a leading cause of cancer-related mortality, with over one million new cases and 769,000 deaths reported in 2020. Despite advancements in chemotherapy, surgery, and targeted therapies, delayed diagnosis due to overlooked early symptoms leads to poor prognosis.MethodsWe integrated bulk RNA sequencing and single-cell RNA sequencing datasets from TCGA, GEO, and OMIX001073, employing normalization, batch effect correction, and dimensionality reduction methods to identify key cell populations associated with GC invasion and epithelial-mesenchymal transition (EMT), as well as analyze the tumor immune microenvironment.ResultsOur analysis identified the MUC5AC+ malignant epithelial cell cluster as a significant player in GC invasion and EMT. Cluster 1, representing this cell population, exhibited higher invasion and EMT scores compared to other clusters. Survival analysis showed that high abundance in cluster 0 correlated with improved survival rates (P=0.012), whereas cluster 1 was associated with poorer outcomes (P=0.045). A prognostic model highlighted ANXA5 and GABARAPL2 as two critical genes upregulated in GC tumors. High-risk patients demonstrated increased immune cell infiltration and worse prognosic. Analysis of tumor mutation burden (TMB) indicated that patients with low TMB in the high-risk group had the worst prognosis. Wet-lab validation experiments confirmed the oncogenic role of ANXA5, showing its facilitation of cell proliferation, invasion, and migration while suppressing apoptosis.ConclusionThis study offers novel insights into the subpopulations of malignant epithelial cells in GC and their roles in tumor progression. It provides a prognostic model and potential therapeutic targets to combat GC, contributing crucial understanding to the fundamental mechanisms of drug resistance in gastrointestinal cancers.